2010
DOI: 10.1007/s11033-010-0222-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of opioids on matrix metalloproteinase-2 and -9 secretion and mRNA levels in MCF-7 breast cancer cell line

Abstract: Matrix metalloproteinases (MMPs) are proteolytic enzymes involved in degradation of extracellular matrix, a process that initiates uncontrolled spread of proliferating cancer cells and therefore plays a crucial role in cancer invasion and metastasis. Compounds able to modulate MMP activity may become important tools in cancer research. In the present study we examined the effect of two μ-selective opioids, morphine and endomorphin-2 (EM-2) on the production of MMP-2 and MMP-9 in MCF-7 cells. We report that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 20 publications
1
31
2
Order By: Relevance
“…A study involving a MCF-7 breast cancer cell line showed the inhibitory effects of MMP induced by morphine (25) , which is in contrast with the results obtained with nalbuphine in the present study. In MCF-7 cells, however, the attenuation of MMP secretion by opioids was not mediated by opioid receptors but was under the con trol of the nitric oxide system (25) . Hormonal factors must be considered when evaluating the effects of opioid analgesics.…”
Section: Discussioncontrasting
confidence: 99%
“…A study involving a MCF-7 breast cancer cell line showed the inhibitory effects of MMP induced by morphine (25) , which is in contrast with the results obtained with nalbuphine in the present study. In MCF-7 cells, however, the attenuation of MMP secretion by opioids was not mediated by opioid receptors but was under the con trol of the nitric oxide system (25) . Hormonal factors must be considered when evaluating the effects of opioid analgesics.…”
Section: Discussioncontrasting
confidence: 99%
“…Gach et al, who found that, morphine exposure to MCF-7 cells at the concentrations of 0.001 to 1 µM altered the expression of MMP-2 and MMP-9 mRNA overexpression and also increased its endogenous inhibitor, altered the proteolytic profile and then inhibited breast tumor cells growth and proliferation. 13) Further, morphine (>500 µm for 24 h) induced significant apoptotic death in MCF-7 and MDA-MB231 cells by blocking β-arrestin-2 through inhibition of caspase-8 pathway. 14) In agreement with these reports, we found potent inhibition on MCF-7 viability and colony formation, which all together indicates better independent anti-proliferative effect of morphine.…”
Section: Discussionmentioning
confidence: 91%
“…Matrix metalloproteases and urokinase type plasminogen activator are known to play a key role in this process. Morphine inhibits matrix metalloprotease (MMP)-2 and MMP-9 expression [24,27] but enhances uPA production [4,28] by breast and colon cancer cells. Invasion into reconstituted basement membrane (Matrigel) was shown to be decreased in colon cancer cells [24] but unchanged in a number of cancer cell lines tested in another study [26].…”
Section: Opioids Alter Tumor Cell Invasionmentioning
confidence: 99%